Politeness Strategies Used by Mario Teguh in Handling Questions in MTGW Program. - Arief, Yusuf Al (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
Mario Teguh was one of the motivators in Indonesia whose fans are considered as the most. He was also issued as the most expensive motivator in Indonesia at this time being. As a great motivator, he must have some strategies to be close and give motivation to his audiences. This research was aimed to figure out the strategies he used, focusing on the strategies for handling questions. The data was collected by observation method and documentation technique. The data was analyzed based on the politeness strategy of Brown and Levinson. From the analysis, I found that at least there were ten strategies used by Mario to share the motivation. These made the audiences did not feel to be lectured when he shared it. In fact, they feel like a friend to him.